PERSEPSI FISKUS TERHADAP FAKTOR-FAKTOR YANG MEMPENGARUHI INDEPENDENSI AUDITOR - ferry laurensius (JAKPI - Jurnal Akuntansi, Keuangan & Perpajakan Indonesia, 2016)
Independence is an impartial mental attitude. This attitude is necessary in order for the opinion of the financial statements to be reasonable and not misleading to the reader of the report. This study analyzes the perception of fiskus who works in a special tax office in the Head Office of Directorate of Taxes, South Jakarta. Data were collected through questionnaires. The data collected were analyzed by calculating the mode and mean of each respondent's answer.The results of the research indicate that the sequence of factors influencing the auditor's independence are: (1) The financial relationship of the Public Accounting Firm with audits and negatively affects the auditor's independence, (2) The audit committee positively affects the auditor's independence, (3) Management consultancy service negatively affects the independence of the auditor, (4) The length of the Public Accounting Firm providing services to auditee negatively affects the auditor's independence, (5) the amount of audit fees negatively affects the auditor's independence.On the basis of the results of the study, auditor must keep maintenace their independence in order to: (1) keep in mind the factors that may affect their independence, (2) auditors avoid financial relationship with audits, (3) Honorary Board of the Indonesian Institute of Accountants should carry out good supervision so there is control for the auditor in maintaining their independence